Construction of interacting flat-band models by molecular-orbital representation: Correlation functions, energy gap, and entanglement. (28th January 2022) - Mizoguchi, Tomonari; Kuno, Yoshihito; Hatsugai, Yasuhiro
Abstract: We calculate correlation functions of exactly solvable one-dimensional flat-band models by utilizing the "molecular-orbital" representation. The models considered in this paper have a gapped ground state with the flat band being fully occupied, even in the presence of the interaction. In this class of models, the space spanned by the molecular-orbitals is the co-space of that spanned by the flat bands. Thanks to this property, the correlation functions are calculated by using the information of the molecular-orbitals rather than the explicit forms of the flat-band wave functions, which simplifies the calculations. As a demonstration, several one-dimensional models and their correlation functions are presented. We also calculate the entanglement entropy by using the correlation function.